Reflecting media content values: media industry attitudes towards Malaysian media self-regulation practices - Syed Alsagoff, Syed Agil; Hassan, Md. Salleh; Hamzah, Azizah; Sulaiman, Nor Hissam (2015)
The popularity of the digital media and the availability of a borderless world of communication networks have formed a new environment, supported by the Information and Communication Technologies (ICT). Along with the Malaysian government’s Multimedia Super Corridor (MSC) projects announcement, A National Communication and Multimedia Policy was introduced, as to encourage the development of industry self-regulatory mechanisms with minimize the costs of regulation while at the same time providing clear guidelines for industry behavior in line with Government policy objectives by implementing the industry voluntary codes of practice. This study identified to what extend the “Self-Regulatory” mechanism for the local media players would benefit the industry and the growth of future media technologies in this country, and the key issues and problems faced by Malaysian Media environment in its attempt to proactively respond to the winds of change breezing through media convergence technology policies and legislations. The study found that there has been an important relationship between the regulators, media industry, and public interest upon the implementation of media self-regulation in Malaysia. The challenges faced by the government and media players upon broadcast and new media content had become a discourse for the both parties to implement best practices of self-regulatory mechanism which allows the self-management of information dissemination for the public and industry interests, and as to ensure to perverse the national identity and cultures.